1990
DOI: 10.1149/1.2086160
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in Electrodeposition of Compositionally Modulated Alloys

Abstract: High-quality specimens of sufficient thickness for reliable testing are needed if the enhanced properties observed for ultrastructured multilayered metals are to be understood and exploited. In the present paper, factors affecting the quality of multilayers electrodeposited from a single electrolyte, via concerted modulation of the electrode potential and electrolyte mass transport, are discussed. The importance of precise control of the potential during deposition of the more noble metal is emphasized. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…Following mechanical properties were mainly investigated: Young's modulus [98], hardness [115], and tensile strength [107,[115][116][117]. It is shown that all investigated properties depend on the thickness of the individual layers and that in all cases multilayered structures showed better properties than that of pure metals and/or their alloys.…”
Section: Mechanical and Magnetic Properties Of Multilayered Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Following mechanical properties were mainly investigated: Young's modulus [98], hardness [115], and tensile strength [107,[115][116][117]. It is shown that all investigated properties depend on the thickness of the individual layers and that in all cases multilayered structures showed better properties than that of pure metals and/or their alloys.…”
Section: Mechanical and Magnetic Properties Of Multilayered Structuresmentioning
confidence: 99%
“…1.46 The hardness of the deposit containing Cu/Ni À 100 layers as a function of the thickness of individual layers (Reprinted from [115] with the permission of Elsevier) Fig. 1.47 The tensile strength of the multilayered deposits as a function of the thickness of individual layers: open circle- [107]; open square- [117]; open triangle- [118]; open inverted triangle- [108] (Reprinted from [109] with the permission of Elsevier) mainly the consequence of different parameters of the deposition process (bath composition, pulse regimes, temperature, etc.). A common explanation for the decrease of tensile strength with the increase of individual layer thickness (after the maximum value) is the increase of the coherence of the intermediate layer.…”
Section: Mechanical and Magnetic Properties Of Multilayered Structuresmentioning
confidence: 99%
“…As soon as the deposited Co layer is completely covered with Au, the deposition process stops. Therefore, the process under open-circuit conditions is defined as a diffusion-controlled reaction that yields no faradic reactions [8,67]. In order to estimate the Au-layer thickness under the open circuit condition, first, a series of Co nanowire samples with a length of 4 mm was deposited during chronoamperometry experiments.…”
Section: Template Synthesis Of 2 Nm Au/4 Nm Co Multilayered Nanowire mentioning
confidence: 99%
“…In the case of longer cylinders (d Co ¼ 50 nm), the axis along the wire starts to become the easy axis (lower saturation field) as expected in the limit where d Ag ¼ 0 (single Co nanowires), due to the shape anisotropy. Again, in both directions, a low remanence was measured leading to an intricate magnetic domain configuration at zero fields [67][68][69][70][71] which requires more characterizations for its elucidation (Figure 4.15).…”
Section: Magnetic Properties Of Nanowire Arraysmentioning
confidence: 99%
“…The presence of less than perfect cylindrical ion track etched pores is related to the statistical nature of the ionization spikes and breaking of chemical bonds in the polymers along the particle trajectory. [27] X-ray diffraction (XRD) analysis of 20 lm thick polycarbonate membranes deposited with 99.9 wt.-% Au and 98 wt.-% Co nanowire arrays are shown in Figure 5. XRD analysis of a virgin membrane with a 500 nm sputter-deposited Au layer was performed and the peaks compared to electrodeposited Au.…”
Section: Deposition Of Pure Au and Co Nanowiresmentioning
confidence: 99%